Analyzing Healing Environment in Post-Operative Units across Selected Hospitals in KPK, Pakistan - Ullah, Ubaid; Khattak, Waqar; Shah, Syed Mazhar Ali (Journal of Art, Architecture and Built Environment, 2022)
Healing environment mainly comprises access to nature, choices and control, positive distractions, absence of environmental stressors, and social support. This research explored the healing environment in the post-operative units in five tertiary level hospitals of KP province, Pakistan. The topic of the current research has not been explored so far in the KP province as Pakistan is a developing country and more research work in the relevant is required. The research was conducted through sample collection from patients through a questionnaire and self-observation of the researcher. A checklist was also used to identify the five basic components of the healing environment. It was established that, on average, only 17% of the patients in post-operative units had access to nature, 21% had choices and control, and 20% were treated with positive distractions. Furthermore, 72% observed the presence of environmental stressors which hindered their healing, while 67% confirmed the availability of social support. Hence, it is evident that healing environment was not a major criterion in the designing of these facilities. The respondents also opted to make these elements available to help the healing process. It was concluded that by increasing the healing environment-based components in post-operative units, better outcomes in terms of healing process may be achieved.